2011
DOI: 10.1155/2011/398945
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Kinetic Properties Associated with Redox Imbalance after Oxidative Crisis in G6PD-Deficient Erythrocytes: A Simulation Study

Abstract: It is well known that G6PD-deficient individuals are highly susceptible to oxidative stress. However, the differences in the degree of metabolic alterations among patients during an oxidative crisis have not been extensively studied. In this study, we applied mathematical modeling to assess the metabolic changes in erythrocytes of various G6PD-deficient patients during hydrogen peroxide- (H2O2-) induced perturbation and predict the kinetic properties that elicit redox imbalance after exposure to an oxidative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…5, 6, 7, 8, 9 However, during the past decade, accumulating evidence has demonstrated that G6PD deficiency also affects nucleated cells 10, 11, 12, 13, 14 and cellular pathophysiological events, including dysregulated cell proliferation, accelerated cellular senescence, enhanced susceptibility to viral infection, and impaired embryonic development. 15, 16 G6PD is essential for normal cell growth and survival.…”
mentioning
confidence: 99%
“…5, 6, 7, 8, 9 However, during the past decade, accumulating evidence has demonstrated that G6PD deficiency also affects nucleated cells 10, 11, 12, 13, 14 and cellular pathophysiological events, including dysregulated cell proliferation, accelerated cellular senescence, enhanced susceptibility to viral infection, and impaired embryonic development. 15, 16 G6PD is essential for normal cell growth and survival.…”
mentioning
confidence: 99%
“…Early models concentrated on defining the reaction-rate as a function of only the products and reactants (G6P, 6PGδL, NADP + , and NADPH). While these models make sense "in the test tube," they miss important important biological regulators seen in vitro and in vivo [39]. Equation 3.1 takes into account some of the biological regulation of G6PD, making it the best equation for studying in vitro and in vivo kinetics.…”
Section: The Reaction Equationmentioning
confidence: 99%
“…Initial Concentration (mM) a G6P 6 NADP + 0.067 NADPH 0 ATP 1.9 2,3-BPG 3.7 a Values for G6P, ATP and 2,3-BPG are physiologic. Physiologic values for NADPH and NADP + are 0.065 mM and 0.002 mM, respectively [39]. 64 M•s −1 a k m values are the concentration of the substrate at which the reaction proceeds at half of it's maximal activity.…”
Section: Chemicalmentioning
confidence: 99%
See 2 more Smart Citations